Song 7:2–6 [Eng: 1–5] as a Symphony of Poetry, Metaphor, and Passion - Chau, K D (Journal for Semitics, 2024)
Song 7:2–6 is (in)famous for how the man describes his beloved, from feet to head, with one seemingly ridiculous metaphor after another. While the aesthetic sense of these metaphors may seem odd to westerners, it was highly unlikely to be such for its original audiences. Thus, the fundamental question for biblical scholars, especially those concerned with metaphor is: How does the poet employ the visual similarities in the metaphorical imagery to allow readers/hearers access to how the man both perceives and conceptualises the physical beauty of his beloved? In other words, how can we as readers take the metaphors seriously without obliterating the metaphorical imagery? This article seeks to answer this question by employing a complexity approach which integrates poetic rhythm (additionally borrowing the concept of deceptive cadence from music), linguistic approaches to poetic parallelism, the use of emotion in lyric poetry, and metaphor analyses. This symphony of analyses hopes to explain how the metaphors function as a unity within the poetry’s rhythm, building toward a peak to express the man’s desire and excitement for his beloved. It concludes by offering an interpretation of the final verse’s interpretively difficult description of the woman’s hair as crimson, explaining how the woman’s head as Mount Carmel during a fiery sunset serves as a fitting conclusion to the poem that provides a befitting climactic closure for conveying the man’s desire for his beloved.